2022
DOI: 10.1515/bmt-2022-0100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EEG brain connectivity of children with ADHD using graph theory and directional information transfer

Abstract: Research shows that Attention Deficit Hyperactivity Disorder (ADHD) is related to a disorder in brain networks. The purpose of this study is to use an effective connectivity measure and graph theory to examine the impairments of brain connectivity in ADHD. Weighted directed graphs based on electroencephalography (EEG) signals of 61 children with ADHD and 60 healthy children were constructed. The edges between two nodes (electrodes) were calculated by Phase Transfer Entropy (PTE). PTE is calculated for five fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The limitations of the current systems prevent their performance in classifying AHDA using the EGG dataset. This is evident from the findings of previous studies [23,24], which reported an accuracy of 93.91% and 91% using SVM and graphic neural networks based on the accuracy measures. Therefore, we have built an upgraded system aimed at boosting the accuracy of the existing method.…”
Section: Introductionsupporting
confidence: 69%
“…The limitations of the current systems prevent their performance in classifying AHDA using the EGG dataset. This is evident from the findings of previous studies [23,24], which reported an accuracy of 93.91% and 91% using SVM and graphic neural networks based on the accuracy measures. Therefore, we have built an upgraded system aimed at boosting the accuracy of the existing method.…”
Section: Introductionsupporting
confidence: 69%
“…Finally, we are taking into consideration connectionism here, because when other theories of mind lack neuroscientific integration [26] and a consequent philosophical coherence, connectionism has been distinctive. After all, it made a strong effort to implement AI and neuroscience into a philosophical theory.…”
Section: Connectionismmentioning
confidence: 99%
“…PLI is useful for studying transient phase synchrony, especially in event-related analysis [63]. T. S. Bearden et al [27] in resting state EEG using the functional magnetic resonance image (fMRI) data of children with ADHD [28][29][30], and FC of default mode network (DMN) and dorsal attention network (DAN) in children with ADHD [31], another example was that [32] combined resting state functional magnetic resonance imaging (rsfMRI) and FC to study the default mode network (DMN). In [32], the event-related potential (ERP) was investigated from childhood to adulthood during cognitive tasks; in another paper, a deep learning model was applied to classify ADHD [24] by using a publicly available fMRI database of adolescents with ADHD.…”
Section: Introductionmentioning
confidence: 99%